Acid and alkaline protease in broiler diets: Effects on weight gain, metabolism and fatty acid profile in meat (Research, Society and Development, 2025)
The objective of this study was to evaluate whether the inclusion of protease (acid and alkaline) in the diet of broiler chickens can improve zootechnical performance, nutrient digestibility, metabolic profile and fatty acids in meat. In this way, an experiment was carried out, with a completely randomized design, with 880 birds, divided into 11 treatments. In relation to meat fatty acids, there was an increase in the concentration of palmitic and palmitoleic acids and monosaturated acids, and a decrease in omegas 3 and 6, polyunsaturated fatty acids, total lipids, and linoleic acid (P > 0.05). For meat quality, the groups with the association of proteases had greater water losses during cooking (P = 0.05). In reaction to villus and crypt, the PL group had the highest villus and crypt ratio (P = 0.02). In conclusion, protease can be used as a feeding strategy, as it allows increased digestibility and gains in zootechnical indexes in diets with lower amounts of protein and amino acids.